Fauna associated with shallow-water methane seeps in the Laptev Sea - Vedenin, Andrey; Kokarev, Valentin; Chikina, Margarita V.; Basin, Alexander B.; Galkin, Sergey V.; Gebruk, Andrey (PeerJ, 2020)
Background Methane seeps support unique benthic ecosystems in the deep sea existing due to chemosynthetic organic matter. In contrast, in shallow waters there is little or no effect of methane seeps on macrofauna. In the present study we focused on the recently described methane discharge area at the northern Laptev Sea shelf. The aim of this work was to describe the shallow-water methane seep macrofauna and to understand whether there are differences in macrobenthic community structure between the methane seep and background areas. Methods Samples of macrofauna were taken during three expeditions of RV Akademik Mstislav Keldysh in 2015, 2017 and 2018 using 0.1 m2 grabs and the Sigsbee trawl. 21 grabs and two trawls in total were taken at two methane seep sites named Oden and C15, located at depths of 60–70 m. For control, three 0.1 m2 grabs were taken in area without methane seepage. Results The abundance of macrofauna was higher at methane seep stations compared to non-seep sites. Cluster analysis revealed five station groups corresponding to control area, Oden site and C15 site (the latter represented by three groups). Taxa responsible for differences among the station groups were mostly widespread Arctic species that were more abundant in samples from methane seep sites. However, high densities of symbiotrophic siboglinids Oligobrachia sp. were found exclusively at methane seep stations. In addition, several species possibly new to science were found at several methane seep stations, including the gastropod Frigidalvania sp. and the polychaete Ophryotrocha sp. The fauna at control stations was represented only by well-known and widespread Arctic taxa. Higher habitat heterogeneity of the C15 site compared to Oden was indicated by the higher number of station groups revealed by cluster analysis and higher species richness in C15 trawl sample. The development of the described communities at the shallow-water methane seeps can be related to pronounced oligotrophic environment on the northern Siberian shelf. ...